PENGARUH FAKTOR SOSIAL, PERSONAL, PSYCHOLOGICAL, DAN KULTURAL TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN CENTRO DEPARTMENT STORE MELALUI STIMULUS MIDNIGHT SALE - Yuriska, Mega Retna; Sukirno, Ign (Modus Journals, 2014)
Midnight sale is one strategy that can provide stimuli to the customer purchase decision.However, the main factor or basis that contribute to the purchase decision by Schifman and Kanuk (2004) as quoted by Samuel, et al., (2005) are social factors, personal factors, psychological factors, and cultural factors. Consumer purchasing decisions due to social factors infuenced by some small groups like, group or group play, family, and the role and status (Kotler and Armstrong, 2004).Tis study was conducted to determine consumers’ assessment of social factors, personal factors, psychological factors, and cultural factors, consumer purchasing decisions knowing that stimulated by midnight sale and determine the infuence of social factors, personal factors, psychological factors, and cultural factors on consumer purchasing decisions Centro Department Store which distimuli by midnight sale. This research was conducted in Yogyakarta, namely the consumers Centro Department Store in June 2013.Te results showed that consumers have a good assessment on social factors, personal factors, psychological factors, cultural factors. Consumers have high purchasing decision in Centro Department Store during a midnight sale promotion program. Social factors, personal factors, psychological factors, and cultural factors simultaneously have a signifcant infuence on consumer purchasing decisions. Social factors, personal factors, psychological factors, and cultural factors have a positive and signifcant impact on consumer purchasing decisions.Keywords: Social factors, Personal factors, psychological factors, cultural factors, purchase decision